2008
DOI: 10.4103/0253-7613.40483
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hypoglycemic effect of Morus alba in an animal model

Abstract: Objective:The objective of the present investigation was to evaluate the therapeutic efficacy of mulberry leaves in an animal model of diabetes.Materials and Methods:Animals were treated with mulberry leaf extract 400 mg and 600 mg/kg body weight for 35 days. Blood glucose, glycosylated hemoglobin, triglyceride, LDL, VLDL, HDL, blood urea, cholesterol, number of β cells, and diameter of the islets of Langerhans were measured at the beginning and at the end of the experiment.Results:Blood glucose level and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 24 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…This indicated that mulberry leaves could be effective to improve glycaemic control and reverse insulin resistance. Moreover, histological examination showed that mulberry leaves treatment restored the size and number of pancreatic β-cells of diabetic animals closely to the baseline levels (Mohammadi and Naik 2008 ).…”
Section: Biological Propertiesmentioning
confidence: 71%
See 1 more Smart Citation
“…This indicated that mulberry leaves could be effective to improve glycaemic control and reverse insulin resistance. Moreover, histological examination showed that mulberry leaves treatment restored the size and number of pancreatic β-cells of diabetic animals closely to the baseline levels (Mohammadi and Naik 2008 ).…”
Section: Biological Propertiesmentioning
confidence: 71%
“… 2011 ). Meanwhile, long-term mulberry leaves ingestion tended to normalize the levels of fasting plasma glucose (FPG), glycated haemoglobin (HbA1c), fructosamine and insulin indexes of diabetic animals to nearly normal values (Mohammadi and Naik 2008 ; Park et al. 2009 ; Kim JY et al.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…In addition, in the acute toxicity evaluation, no toxicity was observed. M. alba extracts have been previously reported to have antihyperglycemic effect in STZ-induced diabetic rats [27] and in diet-induced obese mice [28] and to block inflammatory response in STZ-diabetic mice model [29] and in STZ-induced diabetic rats fed high-fat diet [30]. Among them, Jeszka-Skowron et al have reported that DNJ may suggest additional roles in the gut to reduce or inhibit intestinal glucose digestion and absorption [30].…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] Previous research also indicates that polysaccharides, flavonoids, polypeptides, steroids, alkaloids, and pectin in the medicinal plants can well justify the blood glucose, and cholesterol lipid lowering properties of some herbs in the treatment of diabetes by preventing the blood biochemical changes. [ 26 29 60 61 ]…”
Section: Therapeutic Treatmentmentioning
confidence: 99%
“…[ 16 17 30 ] The results of previous studies shown that walnut administration would change the distribution of lipids in different lipoprotein groups; and the use of walnuts is likely associated with anti-atherogenic effects. [ 60 61 62 63 ]…”
Section: Therapeutic Treatmentmentioning
confidence: 99%